Irene Ximenes e suas narrativas: da Menina da toca à Antígona do Sertão Nordestino - Pontes, Maria Vânia Abreu (2023)
This thesis presents the life story of Irene Ximenes, focusing on her trajectory as Menina da Toca, Menina Insolente and Antígona do Sertão Nordestino. Explore his search for knowledge, fight for Justice in the Ximenes Lopes Case, fight for recognition and his transforming impact on society. The research uses the life narrative as a study method, incorporating for that purpose the use of various sources of research, from a parallax perspective. Authors of Critical Theory, such as Lima, Ciampa, Lane and many others, embark on the methodological questions of the research, allowing a comprehensive understanding of Irene's human condition in its family, social, political, spiritual and artistic dimensions. Irene's performance is highlighted as a narrated social subject and narrator, playing various roles, with remarkable dinners, mainly, as a defender of her brother, Damião Ximenes Lopes, who died during a psychiatric hospitalization at Casa de Repouso Guararapes on October 4 of 1999, in Sobral-CE. Irene creates a legacy through a letter-complaint about the death of her brother, challenging the power structures and raising Brazil to be sentenced by the Inter-American Court of Human Rights. This explores Irene's experiences and struggles, highlighting her strength and resilience in the search for justice and social transformation. This investigation represents a political gesture that emerges from the knowledge of Irene's life trajectory, in which she transforms mourning into a fight for Justice. A differentiated approach to the research positions Irene Ximenes as the protagonist of her own story, challenging academic conventions. Her trajectory of her as a Menina da Toca, Menina Insolente e Antígona do Sertão Nordestino dialogues with critical theory, expanding the theoretical understanding of the research. The study breaks with the traditional position of Irene as a mere provider of information about the Ximenes Lopes Case, revealing her multiple identities and the importance of her voice in the historical process of social transformation.